Multimedia Learning Technology Integration for the Enhancement of Oral Skills in Secondary Education - Fahri Fahri; Fauris Zuhri; Sumarniningsih Sumarniningsih; Fithriyah Inda Nur Abida (Journal of Innovative and Creativity, 2025)
This study aims to evaluate the effectiveness of multimedia integration in improving the speaking competence of junior high school students. Four types of media were systematically implemented video modeling, pronunciation animation, AI-based applications, and digital storytelling within an instructional sequence consisting of input, guided practice, independent practice, and oral production. A mixed-methods approach was employed through pre–post test analysis, as well as student interviews and classroom observations. Quantitative results indicated significant improvement in fluency, accuracy, pronunciation, and confidence. The qualitative findings supported these results, revealing that multimedia enhanced students’ motivation, engagement, and self-confidence in speaking. This study demonstrates that multimedia-based learning is an effective and relevant strategy for teaching speaking at the junior high school level, emphasizing the importance of teacher readiness and digital facility support. The findings provide practical implications for instructional design and open avenues for further research within the context of Indonesian education.